e-Modul Ethnophysics for Critical Thinking Skills in the Covid-19 Pandemic - Lestari, Novika; Apsari, Nurul (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This study describes the development of an integrated ethno-physics module for critical thinking skills as supporting teaching materials during the Covid-19 pandemic. The development stages used were the 4D models. These stages included defining, designing, developing, and disseminating. The subjects of this study were material experts, media experts, and 50 students in Melawi Regency. The instruments were expert validation questionnaires, student perception questionnaires, and critical thinking tests. The resulting data are in the form of qualitative and quantitative data. The expert feasibility test uses the average score to the maximum score, while the user practicality test uses the average eligibility percentage. The trial design used was a pre-test and post-test group design. The statistical test used is parametric statistics with the help of SPSS 26. The study results show that the e-module ethnophysics have validly improved students’ critical thinking skills. This is shown by the results of validity, practicality, and effectiveness of e-module ethnophysics towards critical thinking during the Covid-19 pandemic.